Mechanically induced waves in metallic glass foils - Panagiotopoulos, Nikolaos T.; Yousfi, M. A.; Georgarakis, Konstantinos; Yavari, A. R. (Elsevier, 2015)
The response of vitrified metallic arc foils under normal load is studied. Application of normal load on an initial arc shaped vitrified metallic foil is followed by multiplication of the initial arc. A sinusoidal mathematical expression can be used for the description of the produced harmonic undulations. The number of the formed waves increases as the displacement increases. Therefore, this undulatory behavior of the vitrified foils can be exploited as a flat spring with multiple spring constants. For comparison crystalline foils were tested. The enormous elastic region of vitrified alloys allows this undulatory response to occur extensively while plastic deformation is unavoidable when crystalline foils are used. Exploiting the metallic glass characteristics, the predefined extrem a positions of the formed undulations and the mechanical characteristics of the vitrified foils a new type of electromechanical switch is suggested. (c) 2015 Elsevier Ltd. All rights
Keywords: Electromechanical switch; Buckling; Metallic glasses; Flat springs; Undulatory response; Vitrified metallic foils